2013
DOI: 10.1186/1471-2164-14-514
|View full text |Cite
|
Sign up to set email alerts
|

Confero: an integrated contrast data and gene set platform for computational analysis and biological interpretation of omics data

Abstract: BackgroundHigh-throughput omics technologies such as microarrays and next-generation sequencing (NGS) have become indispensable tools in biological research. Computational analysis and biological interpretation of omics data can pose significant challenges due to a number of factors, in particular the systems integration required to fully exploit and compare data from different studies and/or technology platforms. In transcriptomics, the identification of differentially expressed genes when studying effect(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Increasingly, informatics packages and online portals are being developed that exploit data from multiple sources, taking into account different levels of evidence in a combined way ( Hermida et al, 2013 ). Such machine learning systems are becoming more powerful to compile and mine biomedical information.…”
Section: Weighing the Evidence: Likelihood Of Pathogenicity Scoring Amentioning
confidence: 99%
“…Increasingly, informatics packages and online portals are being developed that exploit data from multiple sources, taking into account different levels of evidence in a combined way ( Hermida et al, 2013 ). Such machine learning systems are becoming more powerful to compile and mine biomedical information.…”
Section: Weighing the Evidence: Likelihood Of Pathogenicity Scoring Amentioning
confidence: 99%
“…Although these 30 microarrays originated from a diverse range of studies, several recent studies [ 60 - 62 ] had suggested that published microarray datasets contain value beyond their initial studies. For example, several studies had analyzed published microarray datasets for reference genes [ 63 , 64 ] and other biologically significant features [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…These bioinformatics and computation tools allow users to integrate and interrogate the datasets in order to observe correlations, to understand interaction networks, and to identify molecular and/or transcriptomic signatures. [160][161][162] One issue with monitoring human immune function is that while blood is the most readily accessible biological specimen, most of the immune response develops in the lymph nodes and site of infection or vaccination. Fagerberg et al have integrated protein expression data from multiple tissue and cell types with transcriptomic analysis in order to create an updated Human Protein Atlas, which will facilitate both in-depth studies of specific tissues, genes, and/or proteins and large scale, systems biology studies.…”
Section: Systems Biology and Predicting Vaccine Responsementioning
confidence: 99%